Occupational Performance in the Discipline of Occupational Therapy During COVID-19 at a Public University in KwaZulu-Natal - N. Ndaba; P. Govender; D. Naidoo (Occupational Therapy International)
Conclusions: This study highlighted the importance of supporting optimal occupational performance among educators and students, emphasizing the necessity of providing adequate resources and support. This ensures the well-being of educators and students, enabling effective engagement and participation as they navigate the evolving educational landscape.